Synergistic combination of ZnCl2/Cu-BTC MOF for the photocatalytic oxidative deamination of benzylamines using CO2 under visible-light irradiation - Kumar, Amod; Bhatt, Sakshi; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Jain, Suman L. (ACS Applied Engineering Materials, 2024)
This paper demonstrates the first CO2-mediated oxidative deamination of benzylamines to benzaldehydes using a combination of ZnCl2 and Cu-BTC MOF as photocatalysts in a carbon tetrachloride solvent under visible-light irradiation. Interestingly, the synergistic combination of ZnCl2 and Cu-BTC afforded the targeted oxidation of benzylamine to benzaldehyde, wherein CO2 acted as an oxidant. The individual components yielded the corresponding imine as the main product, resulting from the oxidative coupling of the benzylamine. DFT calculations and computational studies supported the proposed reaction pathways involving the formation of an intermediate imine from benzylamine via dehydrogenation followed by hydrolysis to produce benzaldehyde. This work, demonstrating the use of CO2 as an oxidant, may open up new avenues for CO2 utilization in chemical production by using sustainable light energy.